2011
DOI: 10.1177/193229681100500309
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Large Diabetes Electronic Medical Record System in India: Clinical and Research Applications

Abstract: Background: The diabetes electronic medical record (DEMR) has emerged as an effective information management tool with the potential to improve diabetes care and research. This study reports on the usefulness of the DEMR system at Dr. Mohan's Diabetes Specialities Centre (DMDSC), Chennai, India, for clinical and research purposes. Methods: The DEMR, set up in 1996 at DMDSC, connects data of nine centers/clinics in different geographical areas in Southern India. The present data analysis is based on a total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 39 publications
0
30
0
Order By: Relevance
“…On the contrary, few other studies reported higher prevalences i.e. 32.5% [14] and 37.9% [15] respectively, probably due to clinic based studies.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…On the contrary, few other studies reported higher prevalences i.e. 32.5% [14] and 37.9% [15] respectively, probably due to clinic based studies.…”
Section: Discussionmentioning
confidence: 49%
“…19.5% [19]. The prevalence of neuropathy in earlier studies from India are 15.3% [01], 26.8% [14], and 33.1% [15] respectively. This variation may be due to glycemic control, genetic susceptibility to develop neuropathy and environmental factors.…”
Section: Discussionmentioning
confidence: 86%
“…To streamline the process of patient referral systems and improve communication, coordination, and data sharing between physicians and other providers, a patient-centered electronic information system is needed [78,79]. The local governments can allocate regional responsibilities to specific tertiary and secondary care centers to ensure that all metropolitan and regional primary health care providers have ready access to specialist multidisciplinary teams for advice, shared care, outreach, and mobile health services.…”
Section: Recommendations For a Comprehensive Diabetes Care Model/progmentioning
confidence: 99%
“…In addition to improving processes and ensuring the quality of patient care, the DEMR also facilitates data mining for clinic-based research. [40] However, such a system is expensive to set up and maintain and is prone to bugs like any other software. Occasionally, use of computerised patient records may detract from the doctor-patient interaction, when the clinician spends more time looking at the computer screen than talking to the patient.…”
Section: Smartphone-based Retinal Photographymentioning
confidence: 99%